Lexicon Dialect Variations of Madurese in the Bangkalan and Sumenep Sociolinguistics Study - Dede Rosyadi ZA; Bima Kurniawan; Nisrinatus Zahiyah; Rosiana Sukma Anjani; Elsa Alfida Maharani (Hasanuddin University, 2025)
This research investigates the lexical variations within the dialects of the Madurese language, with a specific focus on the Bangkalan and Sumenep regions. The study seeks to identify and analyze the ways in which lexical items diverge between these dialects, considering how geographic factors play a role in shaping these variations. Through a descriptive qualitative approach, the study employs a combination of observation, interviews, and field notes to gather comprehensive data. The findings demonstrate that although certain lexical items exhibit differences in form across the dialects, they largely retain the same meanings. These lexical variations are primarily attributed to the geographical separation between the regions, which has led to distinct developments in the Madurese lexicon over time. The research underscores the influence of geographic isolation on the evolution of language and provides a deeper understanding of the dynamic relationship between language and region.